2020
DOI: 10.33988/auvfd.523958
|View full text |Cite
|
Sign up to set email alerts
|

Determination of serum amyloid A, haptoglobin and hepcidin levels in calves with endemic viral pneumonia

Abstract: The aim of this study was to investigate serum amyloid A, haptoglobin and hepcidin levels in respiratory infections caused by various viral agents in calves. Pneumonia is an infectious or non-infectious disease affecting the lungs of all animals, and during the inflammation, blood levels of acute phase proteins increase rapidly. Hepcidin is a hormone that has many functions and is known as type II acute phase reactant. The blood samples were collected from a total of 20 calves to form the study group. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A variety of physiological markers related to the innate immune response have been evaluated for prediction and detection of BRD infection. These have included white blood cell counts [ 28 30 ] interleukins and cytokines [ 31 ] and markers of oxidative stress [ 32 ]. However, across multiple studies, elevated haptoglobin levels have been found to be consistently indicative or predictive of BRD infection [ 29 , 30 , 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of physiological markers related to the innate immune response have been evaluated for prediction and detection of BRD infection. These have included white blood cell counts [ 28 30 ] interleukins and cytokines [ 31 ] and markers of oxidative stress [ 32 ]. However, across multiple studies, elevated haptoglobin levels have been found to be consistently indicative or predictive of BRD infection [ 29 , 30 , 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…These have included white blood cell counts [ 28 30 ] interleukins and cytokines [ 31 ] and markers of oxidative stress [ 32 ]. However, across multiple studies, elevated haptoglobin levels have been found to be consistently indicative or predictive of BRD infection [ 29 , 30 , 32 34 ]. There is moderate evidence for the involvement of cortisol, however, the presence of other stressors in cattle entering a feedlot may limit the effectiveness of cortisol as a BRD biomarker [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination with a respiratory vaccine containing a strong adjuvant has been validated as a model of the inflammatory response induced by BRD (12). The acute-phase protein haptoglobin was elevated in cattle affected by BRD (13)(14)(15)(16)(17) and reached similar levels 24-96 h after vaccination (12). Cortisol was also associated with poor health outcomes in cattle (17, 18), and peaked 2-8 h after vaccination (12).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study demonstrated that CRP could achieve a sensitivity of 74.5% and specificity of 81% for readmission events among AECOPD patients. 6 Among new biomarkers investigated, serum amyloid A (SAA), which is a polygenic encoded acute temporal response protein, has stood out as patients in the early stage of viral pneumonia, 8 early non-invasive bacterial pneumonia, 9 COVID19, 10 rheumatic diseases, 11 etc.…”
Section: Introductionmentioning
confidence: 99%